2017
DOI: 10.3389/fcimb.2017.00264
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Endometrial Epithelial Cells Scale Their Pro-inflammatory Response In vitro to Pathogenic Trueperella pyogenes Isolated from the Bovine Uterus in a Strain-Specific Manner

Abstract: Among different bacteria colonizing the bovine uterus, Trueperella pyogenes is found to be associated with clinical endometritis (CE). The ability of cows to defend against T. pyogenes infections depends on the virulence of invading bacteria and on the host's innate immunity. Therefore, to gain insights into bacterial factors contributing to the interplay of this host pathogen, two strains of T. pyogenes were included in this study: one strain (TP2) was isolated from the uterus of a postpartum dairy cow develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
0
13
1
4
Order By: Relevance
“…Nevertheless, the biopsy samples from the metritic cows seem to form a subgroup of the swab metritic communities. This observation can be explained by the different tissue penetrating abilities certain bacteria possess, by which only some members of the metritic bacterial communities found in the lumen and barrier epithelium can actually invade the uterine wall and cause disease [ 20 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the biopsy samples from the metritic cows seem to form a subgroup of the swab metritic communities. This observation can be explained by the different tissue penetrating abilities certain bacteria possess, by which only some members of the metritic bacterial communities found in the lumen and barrier epithelium can actually invade the uterine wall and cause disease [ 20 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a former study was shown that the strain L. buchneri DSM 32407 did neither influence the viability of endometrial epithelial cells nor provoke a pro-inflammatory response in contrast to other Lactobacillus strains 16 . Pathogenic ( Trueperella pyogenes ) or potential pathogenic strains ( Bacillus pumilus ) caused cell death even within 16–24 h 33 , 34 . Therefore, the strain L. buchneri DSM 32407 seems suitable to serve as a probiotic strain within the bovine uterus to modulate the immune response and the reproductive performance of dairy cows.…”
Section: Discussionmentioning
confidence: 99%
“…In the first passage, endometrial epithelial cells were cultured in 96‐well plates until their density reached 3 × 10 5 cells/mL in a humidified incubator at 37°C and 5% CO 2 for 24 hours to make the cells adjust to conditions. In the second passage, the uterine epithelial cell population was observed to reach a 100.0% pure epithelial cell population, the medium was removed again, and the endometrial epithelial cells were washed three times with PBS as described by Ibrahim et al After 72 hours of incubation, nisin and kanamycin were diluted with PBS to 6.22 μg/mL and 0.25 μg/mL, respectively, and suspended in an antibiotic‐free epithelial cellculture medium before being cocultured with the endometrial epithelial cells and S aureus . ELISA kit and RT‐PCR were used to determine the cytokine levels of the uterine epithelial cell culture supernatants (UEC).…”
Section: Methodsmentioning
confidence: 99%
“…The RT‐PCR conditions consisted of 95°C for 10 minutes (45 cycles), followed by 45 cycles at 95°C for 15 seconds, 20 seconds of annealing at a temperature specified for each gene, and a last step at 72°C for 30 seconds. This was followed by a melting curve program (50‐90°C) and a final cooling step at 40°C for 1.0 minutes …”
Section: Methodsmentioning
confidence: 99%